412 Prevalence of pulmonary hypertension in patients referred for sleep apnea diagnostics. (3rd May 2021) - Elfimova, Eugeniya; Mikhailova, Oxana; Danilov, Nikolai; Litvin, Alexander; Pevzner, Alexander; Chazova, Irina
Abstract: Introduction: The aim to evaluate the prevalence of pulmonary hypertension according to echocardiography in patients referred for sleep apnea diagnostics. Methods: We included 145 patients referred to Sleep laboratory for sleep apnea diagnostics. Mean age 63, 8 ± 10, 4 years, BMI 34, 0 ± 5, 7 kg/m2, AHI 31, 3 ± 20, 3/h, ODI 3% 28, 2 ± 19, 5/h, min SpO2 77, 4 ± 9, 8%, systolic pulmonary artery pressure (systolic PAP) 25, 9 ± 16, 4 mmHg. All patients underwent cardiorespiratory and respiratory diagnostics for sleep apnea and echocardiography. Results: From the random sample of patients referred to Sleep laboratory 14, 5% (21) had systolic PAP > 40 mmHg (by echocardiography). Patients with higher levels of systolic PAP (Systolic PAP, mmHg 49, 9 [43, 6; 56, 2] vs 20, 7 [19, 9; 23, 5], p=0.000) had more severe OSA (AHI 35, 7 [27, 1; 44, 3] vs 26, 6 [22, 6; 30, 6], p = 0.029, ODI 3%, /h 35, 8 [25, 1; 46, 4] vs 23, 8 [19, 8; 27, 8], p= 0.017) and were more obese (BMI 37, 1 [33, 8; 40, 4] vs 33, 4 [32, 4; 34, 5], p=0.024). Prevalence of AHI > 30 /h was 62% in group with systolic PAP > 40 mmHg vs 23% in the group with systolic PAP < 40 mmHg. We observed differences in echocardiography, in group with systolic PAP > 40 mmHg: left atrium (4.6 ± 0, 5 vs 4, 2 ± 0, 4 cm, p=0.012), left atrium volume (94.0 ± 23.6 vs 71.7 ± 16.5 ml, p=0.001) and right atrium area (24.5 ± 4.9 vs 18.4 ± 3.8cm2, p=0.000) were higher. Though ejection fraction (58.2 ± 3.8 vs 59.0 ± 3.8%, p=0.268), interventricular septum thickness (1, 13 ± 0, 2 vs 1, 06 ± 0, 3 cm, p=0, 654) and left ventricular posterior wall thickness (1, 05 ± 0, 08 vs 1, 00 ± 0, 13 cm, p=0, 117) didn't differ. In terms of excessive daytime sleepiness, snoring and nocturia groups didn't differ, as well as for the prevalence of arterial hypertension, coronary artery disease, chronic heart failure, diabetes mellitus and chronic obstructive pulmonary disease. Conclusion: Pulmonary hypertension is frequently observed in patients with OSA and appears to be related to the severity of sleep apnea and obesity. PH should be considered in the regular clinical assessment of all patients with sleep apnea, especially with severe form. Support (if any):